Rethinking Parties in Democratizing Asia - Teehankee, Julio C.; Echle, Christian (Taylor & Francis, 2023)
Looking at eight case studies of Asian democracies, the contributors to this volume analyze the role of political parties in stabilizing and institutionalizing democracies. How have democracies such as Indonesia, Sri Lanka, and the Philippines survived against the odds, despite struggling economic performance and highly unequal distribution of income? How have formerly authoritarian regimes in places like South Korea and Taiwan evolved into stable democracies? The contributors to this volume examine these case studies, along with Mongolia, Malaysia, and India, arguing that the common element is the extent to which political parties, including opposition parties, have become institutionalized and act as stabilizers on democracy. They contend that the role of political parties has been significantly underestimated in comparison with structural elements, which are insufficient to explain how these democracies have persisted. An essential resource for students and scholars of Asian politics, especially those with a focus on comparative politics, political parties, and institutions.